Chemotherapy Drug Extravasation in Totally Implantable Venous Access Port Systems: How Effective is Early Surgical Lavage?. Issue 1 (January 2015) - Azaïs, Henri; Bresson, Lucie; Bassil, Alfred; Katdare, Ninad; Merlot, Benjamin; Houpeau, Jean-Louis; Bedoui, Sophie El; Meurant, Jean-Pierre; Tresch, Emmanuelle; Narducci, Fabrice
Purpose: Totally implantable venous access port systems (TIVAPS) are a widely used and an essential tool in the efficient delivery of chemotherapy. Chemotherapy drug extravasation (CDE) can have dire consequences and will delay treatment. The purpose of this study is to both clarify the management of CDE and show the effectiveness of early surgical lavage (ESL). Methods: Patients who had presented to the Cancer Center of Lille (France) with TIVAPS inserted between January 2004 and April 2013 and CDE had their medical records reviewed retrospectively. Results: Thirty patients and 33 events were analyzed. Implicated agents were vesicants (51.5%), irritants (45.5%) and non-vesicants (3%). Huber needle malpositionning was involved in 27 cases. Surgery was performed in 97% of cases, 87.5% of which were for ESL with 53.1% of the latter requiring TIVAPS extraction. Six patients required a second intervention due to adverse outcomes (severe cases). Vesicants were found to be implicated in four out of six severe cases and oxaliplatin in two others. Extravasated volume was above 50 ml in 80% of cases. Only one patient required a skin graft. Conclusions: CDEs should be managed in specialized centers. ESL allows for limited tissue contact of the chemotherapy drug whilst using a simple, widely accessible technique. The two main factors that correlate with adverse outcome seem to be the nature of the implicated agent (vesicants) and the extravasated volume (above 50 ml) leading to worse outcomes. Oxaliplatin should be considered as a vesicant.